The analysis of uncertainty factors influence on mathematical modeling of ammonia compression in wet vapor area - D. Kh. Sadvakasov; G. I. Chernov; V. L. Yusha (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The paper presents the influence analysis of such uncertainty factors as the heat transfer coefficient calculation method and the working chamber wall temperature on the mathematical modeling of the ammonia compression in a reciprocating compressor stage during the condensation of ammonia vapors. The mathematical model is based on the equation of the first law of thermodynamics for bodies with variable mass, the equation of state for real gases, the Clausius–Clapeyron and Newton–Richman equations. When determining the heat transfer coefficient value, several well-known dependencies for calculating these coefficients for dropwise and filmwise condensation have been considered. The calculation data shows that the instantaneous values of the ammonia pressure and temperature, as well as of the dryness fraction during compression in the wet steam region, significantly depends on the chosen method for calculating the heat transfer coefficient. Moreover, the walls temperature value of the compressor working chamber, where the compression occurs, has a considerable impact on the process under discussion. They are the determining factors and require special attention when the ammonia compression process is mathematically modelled in a reciprocating compressor stage, taking into account its vapors condensation.